Removal of a broken acupuncture needle in retroperitoneum by laparoscopy: a case report - Zhen-Hua Liu; Hai-Dong Wang; Xiao Xu; Li-Bo Man (BMC Surgery, 2019)
Abstract Background Acupuncture is a famous traditional medicine in China, but the complications caused by broken acupuncture needles have been rarely reported. It seems easy to remove the foreign matters usually, but things become difficulty in special issues. Here, we reported a recently encountered case to provide an important teaching point of treating a chronically retained broken needle in retroperitoneum. Case presentation A 42-year-old man presented with a chronically retained broken needle in his body after acupuncture therapy two years ago. However, due to the discomfort at the left back recently and ordinary inconvenience such as security check, he came to our hospital for minimally invasive surgery. He was introduced to our department because the broken needle had migrated from subcutaneous to adipose tissue in retroperitoneum during the two years. Considering the position of the broken needle, the patient was performed by laparoscopy in general anesthesia. The operation time was about 31 min and there were only three 7 mm incisions in the left lateral abdominal wall. The X-ray exam was performed to confirm that the broken needle was removed integrally. The patients begun normal activity at 6 h after surgery and was discharged on the second day after surgery. Conclusions Acupuncture is widely used for pain treatment in China, but how to handle the complication of acupuncture needle broken in body are rarely reported. Laparoscopy will be the reasonable choice for treating needles broken in retroperitoneum.